Oil spill absorbent from natural materials / Prof. Madya Dr. Ku Halim Ku Hamid and Puan Dayang Aishah Abang Chi - Ku Hamid, Ku Halim; Abang Chi, Dayang Aishah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2004)
Three types of natural materials were studied to produce low cost oil spill absorber i.e. rice husk, peat and coconut dreg. The raw materials were carbonised before being soaked with 1 M HCI or soaked with methanol.